Analisis Framing Terhadap Pemberitaan Pelatih Timnas Indonesia - Wijanarko, Rana Aqila; Nadhifa, Fairuz Hasna (Universitas Al Azhar Indonesia, 2022)
arious media publish sports news for sports lovers to enjoy. Each media and news portal certainly has a unique way of delivering, writing and uploading the news. This article was written by researchers to find out how the Kompasiana media framed a news story about the Indonesian national team coach, Shin Tae Yong. Many media have highlighted Shin Tae Yong's behavior in coaching the Indonesian national team and the positive and negative influences that had an impact on the Indonesian national team when Shin Tae Yong became the coach of the Indonesian national team. The writing of this article uses a framing analysis approach with a qualitative method. The framing analysis model used is Zhongdang Pan and Gerald M. Kosicky. The results obtained from writing this article are the Kompasiana media news portal framing Shin Tae Yong to have a positive side and a fairly good strategy for Indonesia's victory to be proud of. Meanwhile, CNN frames Shin Tae Yong in a different way so that it can lead the opinion of sports lovers, especially in terms of football.